Induction of Osteopontin by Dengue Virus-3 Infection in THP-1 Cells: Inhibition of the Synthesis by Brefelamide and Its Derivative - Pascapurnama, Dyshelly N.; Labayo, Hannah K. M.; Dapat, Isolde; Nagarajegowda, Divya D.; Zhao, Jingge; Zhang, Jing; Yamada, Osamu; Kikuchi, Haruhisa; Egawa, Shinichi; Oshima, Yoshiteru; Chagan-Yasutan, Haorile; Hattori, Toshio (Frontiers in Microbiology, 2017)
Osteopontin (OPN) is a multifunctional matricellular protein produced by a broad range of cells including osteoclasts, macrophages, T cells, endothelial cells, and vascular smooth muscle cells. OPN modulates various physiological and pathological events such as inflammation, wound healing, and bone formation and remodeling. Dengue virus (DENV) infection causes an increase in plasma OPN levels, which is correlated with the severity of symptoms and coagulation abnormalities. DENV infection also induces OPN gene expression in human macrophages. This study investigated the inhibitory effects of brefelamide and its methyl ether derivative on DENV-3 by measuring changes in OPN levels in human THP-1 and 293T cell lines infected at different multiplicities of infection and post-infection time points. OPN mRNA expression and viral RNA were detected by reverse transcriptase quantitative real-time PCR, whereas protein level was determined by enzyme-linked immunosorbent assay. We found that viral copy number was higher in 293T than in THP-1 cells. However, THP-1 constitutively expressed higher levels of OPN mRNA and protein, which were enhanced by DENV-3 infection. Brefelamide and its derivative suppressed OPN production in DENV-3 infected THP-1 cells; the effective doses of these compounds had no effect on uninfected cells, indicating low cytotoxicity. These results suggest that brefelamide and its methyl ether derivative have therapeutic effects in preventing inflammation, coagulopathy, and fibrinolysis caused by OPN upregulation induced by DENV-3 infection.